Geographical distribution, genetic diversity, and environmental adaptations of dromedary camel breeds in Saudi Arabia - Ibrahim, Mohanad A.; Tolone, Marco; Barbato, Mario; Alsubaie, Faisal M.; Alrefaei, Abdulwahed Fahad; Almutairi, Mikhlid (Frontiers in Veterinary Science, 2025)
The dromedary camel (Camelus dromedarius) in Saudi Arabia exhibits significant genetic diversity, driven by adaptation to diverse ecological niches such as deserts, mountains, and coastal areas. This study explores the genetic structure of these camel populations, correlating their genetic diversity with geographical regions rather than ecological classifications. Through whole-genome sequencing of 63 camel genomes, we identified substantial differences in heterozygosity and inbreeding across different ecotypes, particularly noting higher genetic diversity in mountainous populations and lower diversity in coastal populations. The study also revealed significant enrichment of specific gene sets associated with environmental adaptation, such as the HECT domain in desert populations, which is crucial for maintaining protein integrity under extreme conditions. Principal component and admixture analyses further highlighted the genetic distinctiveness of certain breeds, particularly the Awarik (beach ecotype), which showed signs of genetic isolation.